Accessibility and inclusivity of Volunteers with disability for Sport Events : A Case of Paris 2024 volunteer Programme. - Noirot, Marie-Lou Jeanne (Πανεπιστήμιο Πελοποννήσου, 2025)
Volunteers are crucial for the success of any event, particularly in sports. They ensure the sustainability of the sport movement and bring benefits to both participants and society. This study examines how a mega sport event volunteer programme can enhance accessibility and inclusivity for disabled individuals. Using qualitative research, the study focuses on disability, inclusion, and accessibility in sport, with a case study on the Paris 2024 volunteer programme. Interviews were conducted with disabled volunteers and workforce managers involved at different stages of the organisation. Preliminary findings indicate Paris 2024 is pioneering in dedicating a person solely to accessibility, though full inclusion requires significant resources. Volunteers with invisible disabilities reported more negative experiences. Training for welcoming people with disabilities has improved but still falls short of Paris 2024's goals. The strategy needs to be integrated into every step of the volunteer process, with ongoing training and a dedicated focus on accessibility. Additionally, organizations must reach out to potential volunteers with disabilities, promoting inclusivity through clear messaging and partnerships with relevant groups. One of the main highlight is the dynamic between the volunteer management team and volunteers with disabilities, emphasizing the necessity for close collaboration to achieve a better understanding of how and when to work together effectively.
Keywords: Αθλητισμός για άτομα με ειδικές ανάγκες; Αθλητικές διοργανώσεις; Ειδικά γεγονότα - Διοίκηση και οργάνωση; Παραολυμπιακοί αγώνες; Ολυμπιακοί Αγώνες; Εθελοντισμός; Διακρίσεις στον αθλητισμό; Άτομα με ειδικές ανάγκες - Ενσωμάτωση; Ολυμπισμός Κίνητρο (Ψυχολογία); Sports for people with disabilities; Sports tournaments; Special events - Management; Paralympic Games; Olympic Games; Volunteering; Discrimination in sports; Integration of people with disabilities; Olympism; Motivation (Psychology); Volunteerism; Disability; Accessibility; Inclusivity; International Sport Events; Sport Volunteers; Olympic Games; Paralympic Games; Olympism; Sport Event Volunteers